2017
DOI: 10.4103/0366-6999.204097
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Brain Tissue Monitoring after Semi-brain Irradiation in Rats Using Proton Magnetic Resonance Spectroscopy

Abstract: Background:In head and neck neoplasm survivors treated with brain irradiation, metabolic alterations would occur in the radiation-induced injury area. The mechanism of these metabolic alterations has not been fully understood, while the alternations could be sensitively detected by proton (1H) nuclear magnetic resonance spectroscopy (MRS). In this study, we investigated the metabolic characteristics of radiation-induced brain injury through a long-term follow-up after radiation treatment using MRS in vivo.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A spectrophotometer was used to read the absorbance of each well at 450 nm, and the contents of each well were calculated by using a standard curve. [14] 2.4 | Quantitative measurement of blood proinflammatory cytokines…”
Section: Determination Of Antioxidants and Oxidative Stress Parametmentioning
confidence: 99%
“…A spectrophotometer was used to read the absorbance of each well at 450 nm, and the contents of each well were calculated by using a standard curve. [14] 2.4 | Quantitative measurement of blood proinflammatory cytokines…”
Section: Determination Of Antioxidants and Oxidative Stress Parametmentioning
confidence: 99%
“…MRS can be used to monitor brain tumor progression and is helpful for identifying radiation necrosis after radiation therapy [22,23]. In studies of radiation brain damage, MRS has been shown to detect early metabolic changes in normal irradiated brain tissue [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the early metabolic characterization of brain tissues following irradiation may present clues to the mechanism of radiation‐induced brain injury and modify the therapeutic strategy. In recent years, magnetic resonance spectroscopy (MRS) has been used to measure the metabolic changes in radiation‐induced brain injury, and has suggested that choline/creatine and N ‐acetylaspartate/creatine are significantly decreased in clinical patients and rats following irradiation (Chen, Cheng, & Zhou, ; Bálentová et al, ; Sundgren et al, ). However, the earliest time point of monitoring these changes based on MRS was at week 3 of radiation exposure (Sundgren et al, ).…”
Section: Introductionmentioning
confidence: 99%